A variable structure observer for the control of robot manipulators - Abdessameud, Abdelkader; Khelfi, Mohamed Fayçal (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the application of a variable structure observer developed for a class of nonlinear systems to solve the trajectory tracking problem for rigid robot manipulators. The analyzed approach to observer design proposes a simple design methodology for systems having completely observable linear parts and bounded nonlinearities and/or uncertainties.
Keywords: variable structure observers; switching-type observers; rigid robot manipulators; exponential stability; tracking control